Certain aortic geometries and hemodynamics are associated with FID development and impact the evolution of uncomplicated type B intramural hematoma during the acute phase. Issue 5 (1st April 2019) - Jiang, Dandan; Kuang, Feng; Lai, Yiquan; Shan, Zhonggui; Chen, Qu
Abstract: Objectives: It is difficult to predict the evolution of uncomplicated type B intramural hematoma (IMHB) with a focal intimal disruption (FID) in the acute phase. The aims of this study were to investigate the predictors of FIDs and summarize the risk factors for the evolution of uncomplicated IMHB in the acute phase. Methods: Eighty‐six patients with uncomplicated IMHB were included and were divided according to the development of an FID during the acute phase: the FID group ( n = 32) and the no‐FID group ( n = 54). Geometric measurements and computed fluid dynamic calculations were based on a computed tomography scan performed on admission. Multivariate logistic regression analysis was used to estimate the predictors of FID development. Results: Thirty‐two (37%) patients developed an FID. Patients with an FID had higher C‐reactive protein levels (18.6 ± 2.3 vs 8.1 ± 0.2 mg/dL, P < 0.001) and white blood cell counts (10.3 ± 2.1 vs 7.5 ± 1.7 10 9 /L, P < 0.001). The no‐FID group had lower occurrences of disease progression (15% vs 64%, P < 0.001) and aorta‐related mortality (6% vs 25%, P = 0.016). Multivariate logistic regression analysis indicated a significant risk for the occurrence of an FID with a larger maximum aortic diameter (OR, 1.35; 95% CI, 1.05‐1.73, P = 0.020), thicker hematoma (OR, 2.20; 95% CI, 1.40‐3.48, P = 0.001), and higher oscillatory shear index (per 0.01 unit, OR, 1.74; 95% CI, 1.21‐2.49, P = 0.003). The aorta‐related mortality during the acute phase was 25% (n = 8). Conclusions: Certain aortic conditions, including ta larger aortic diameter, thicker hematoma and higher oscillatory shear stress, are associated with the FID development and result in worse clinical outcomes.